(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper examines the influence of digital inclusion in the social and work place integration of inmigrants in Spain, and in particular for the establishment ofso-called ‘mestiza2 enterprises’. An analysis model was used that brings together (i) the possibilities in the use of ICT by inmigrants and their employers, (ii) their capacity to use them (an expression of demand), and (iii) available ICT resources (anexpressión of supply), in order to characterize desirable e-inclusion processes forinmigrants. New actors are identified (like the emergent and networked Diasporas), as well as new mechanisms (such as Corporate Social Responsibility for diversitymanagement). Finally, a routing matrix is proposed that links involved actors (eg.Public Administration, companies, Diasporas, etc.) with action areas (eg. training,knowledge management, policies, etc.) in order to identify possible activities in eachcase.